Verification Process for DPD Member Candidacy in Riau Province Through The SILON Application in 2024 - Anang Prayogi, Muhammad; Yandra, Alexsander; Nasution, Sri Roserdevi; Hadry, Rusly; Zulkifli, Afni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Research shows that the process of verifying the candidacy of DPD members in Riau Province through the SILON application effectively improves the efficiency of election administration. However, in reality, a number of problems have arisen that need attention. One of the main problems identified as evidence from the research is disruption to access to the SILON server, which causes delays in document verification and confirmation of registrant status, so that the verification process does not run smoothly according to the set schedule. Additionally, the lack of understanding and skills in using SILON among human resources within the Riau Provincial Election Commission (KPU) also acts as a barrier, as both technical and non-technical obstacles affect the accuracy and speed of data input and document verification. These findings indicate that while SILON technology can enhance administrative efficiency, the need for improvements in technological infrastructure and user capacity is crucial to optimizing SILON's role as a digital democracy tool. The implications of these findings emphasize the need for improved technical infrastructure, efforts to restore and maintain more stable server access, and ongoing training programs for human resources to ensure that candidate verification can be conducted accurately, on time, and responsively to the dynamics of the election.